Pengaruh Fraud Triangle dan Integritas Terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi Di Kota Semarang - Hidayani, Hidayani; Setiyono, Taufiq Andre Setiyono (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of the fraud triangle (pressure, opportunity, rationalization) and integrity on academic fraud among accounting students in Semarang City. The population in this study were undergraduate accounting students enrolled at universities in Semarang City, both public and private. A purposive sampling technique was used to select 100 accounting students. Data were collected through online questionnaires distributed to respondents via Google Forms. This study employed a quantitative approach with SPSS statistical analysis methods, including validity tests, reliability tests, and multiple linear regression analysis. The results showed that pressure had a significant positive effect, opportunity had a non-significant positive effect, rationalization had a significant positive effect, and integrity had a significant negative effect on academic dishonesty among accounting students in Semarang City. This study provides an understanding of the motivations for academic fraud and suggests steps to prevent academic fraud.